Meninjau Kembali Persoalan Hukum Kerangka Peraturan Penataan Ruang Kota Di Indonesia - Zulkaidi, Denny (Center for Research and Community Services ITB, 1995)
The provision of regulatory framework for urban planning in Indonesia still needs to be discussed. Though the Spatial Planning Act of 1992 has amended the SVO 0f 1948, there are a number of legal aspect problems that have not been touched on or solved by those Act These problems include incomplete urban planning provisions in the Spatial Planning Act, unavailability of implementing government regulations as designated in the Act, improver form of legislation, and incoherence urban planning related legislation. Regarding these problems, urban planning regulatory framework should immediately perfected and completed.